Attention (to Virtuosity) Is All You Need: Religious Studies Pedagogy and Generative AI - Barlow, Jonathan; Holt, Lynn 1959- (2024)
The launch of ChatGPT in November of 2022 provides the rare opportunity to consider both what artificial intelligence (AI) is and what human experts are. In the spirit of making the most of this opportunity, we invite the reader to follow a suggestive series of “what if” questions that lead to a plausible settlement in which the human expert and the generative AI system collaborate pedagogically to shape the (human) religious studies student. (1) What if, contrary to the Baconian frame, humans reason primarily by exercising intellectual virtuosity, and only secondarily by means of rules-based inference? (2) What if, even though we train AI models on human-generated data by means of rules-based algorithms, the resulting systems demonstrate the potential for exercising intellectual virtuosity? (3) What if, by deprioritizing mechanistic and algorithmic models of human cognition while being open to the possibility that AI represents a different species of cognition, we open a future in which human and AI virtuosos mutually inspire, enrich, and even catechize one another?
Keywords: Pedagogy; Religious Studies; philosophy of science; Virtue epistemology; generative artificial intelligence